PERJANJIAN NOMINEE DALAM HUKUM PERTANAHAN INDONESIA - Annisa Maudi Arsela; Febby Mutiara Nelson (UNIVERSITAS PAKUAN, 2021)
ABSTRACT In the use of nominee agreements, it should be strictly regulated and prohibited in land legislation in Indonesia. This is considered to be the spearhead of the protection and legal certainty of land ownership rights. The use of this nominee agreement is considered to have violated the land registration system and the land publication system that has been regulated in Law Number 5 of 1960 concerning Basic Agrarian Regulations and Government Regulation of the Republic of Indonesia Number 24 of 1997 concerning Land Registration. However, in practice this nominee agreement is deemed to have developed and will continue to develop in people's lives in Indonesia, bearing in mind that in social life there will continue to be interactions and socializing. In this case, this interaction will lead to a collaboration between individuals which will be stated in an agreement that can lead to nominee agreements, especially in the land sector in Indonesia. Given that there is a principle of freedom of contract in the legal system adopted in Indonesia, it is undeniable that in practice in society we can find the development of nominee agreements that will develop and increase in number if there is no regulation regarding this matter which is contained in positive law in effect in Indonesia. Key words: Agreement, Nominee, Land. ABSTRAK Dalam penggunaan perjanjian nominee seharusnya diatur dan dilarang secara tegas dalam perundang-undangan pertanahan di Indonesia. Hal ini merupakan ujung tombak dari perlindungan dan kepastian hukum terhadap hak kepemilikan atas tanah. Penggunaan perjanjian nominee ini dirasa telah menyalahi sistem pendaftaran tanah dan sistem publikasi tanah yang sudah diatur dalam Undang-Undang Nomor 5 Tahun 1960 tentang Peraturan Pokok Dasar Agraria dan Peraturan Pemerintah Republik Indonesia Nomor 24 Tahun 1997 Tentang Pendaftaran Tanah. Namun dalam prakteknya perjanjian nominee ini dirasa telah berkembang dan akan terus berkembang dalam kehidupan masyarakat di Indonesia, mengingat dalam kehidupan bermasyarakat akan terus melakukan interaksi dan bersosialisasi. Dalam hal ini dengan adanya interaksi tersebut akan menimbulkan suatu kerjasama antar individu yang akan dituangkan dalam suatu perjanjian yang dapat menimbulkan perjanjian nominee terlebih dalam bidang pertanahan di Indonesia. Mengingat bahwa terdapat asas kebebasan berkontrak dalam sistem hukum yang dianut di Indonesia maka tidak dapat dipungkiri dalam praktiknya di masyarakat dapat kita temukan perkembangan perjanjian nominee yang akan semakin berkembang dan semakin banyak apabila tidak ada pengaturan mengenai hal tersebut yang dituangkan dalam hukum positif yang berlaku di Indonesia. Kata kunci: Perjanjian, Nominee, Pertanahan.